Improving pain management in a neonatal intensive care unit with single‐family room—A quality improvement project - Lene Tandle Lyngstad; Solfrid Steinnes; Flore Le Marechal (Paediatric & Neonatal Pain, 2022)
Abstract Preterm birth is a risk factor for early experience of pain. Despite advances in neonatal care, evidence‐based knowledge of the importance of adequate pain management and strong international guidelines for assessment and treatment of neonatal pain, only 10% of sick term and preterm infants were assessed for pain and stress on a daily basis. The aim of this quality improvement (QI) project is evaluation of implemented guidelines for pain assessment and management, and increased parental involvement in a Norwegian single‐family room NICU. Method: The different steps of the project entailed translation of the English version of COMFORTneo, development and implementation of guidelines with flowcharts for pain management, and pain assessment certification of the interprofessional staff. Part two of the project is supervision of the interprofessional staff in parental involvement in stress‐ and painful procedures. Our study showed that one year after implementation, 88.8% of the COMFORTneo assessments were performed according to the pain management guidelines. The staff used the flowcharts to assess, treat and reassess pain and stress. There was a high interrater reliability with linearly weighted Cohen's kappa values ranging from 0.81 to 0.95, with a median of 0.90. In addition, our study showed increased parental involvement in procedures, from 50.3% before to 82.3% after the quality improvement project. The success of this quality improvement project is explained by systematic use of flowcharts and implemented guidelines for pain management, interprofessional collaboration, and cultural change agents. Theoretical lectures and practical bedside supervision to interprofessional staff increased parental involvement in stress‐ and painful procedures.